Solving Box Constrained Variational Inequalities by Using the Natural Residual with D-Gap Function Globalization - Fukushima, Masao; Kanzow, Christian (My University, 1997)
We present a new method for the solution of the box constrained variational inequality problem, BVIP for short. Basically, this method is a nonsmooth Newton method applied to a reformulation of BVIP as a system of nonsmooth equations involving the natural residual. The method is globalized by using the D-gap function. We show that the proposed algorithm is globally and fast locally convergent. Moreover, if the problem is described by an affine function, the algorithm has a finite termination property. Numerical results for some large-scale variational inequality problems are reported.
Keywords: finite termination; quadratic convergence; global convergence; Newton's method; D-gap function; natural residual; mixed complementarity problem; variational inequality problem